Research on Intelligent Temperature Control Technology for Spacecraft with Instantaneous High Power Load. Issue 1 (April 2021) - Wang, Jin; Gong, Mengmeng; Zhu, Shanglong; Zhang, Qun; Chen, Yi; Li, Defu; Deng, Wan; Qi, Feng
Abstract: Thermoelectric modules are widely studied by domestic and foreign experts and scholars because of their light weight, small size, absence of mechanical moving parts, and the ability to switch between cooling and heating and adjust the cooling/heating capacity by current. Based on the advantages of thermoelectric modules, this paper proposes an innovative thermoelectric module-based intelligent temperature control device for instantaneous high-power payloads of spacecrafts, which can realize the rapid heat dissipation of high power payloads and adjust the current of thermoelectric modules through intelligent temperature control strategies to precisely regulate the payload temperature. The results show that the thermal control device can efficiently control the heat of the instantaneous high power load during the orbit, and the precision temperature control of the thermoelectric cooling work during the load operation is achieved with the temperature control accuracy of ±0.5°C.